The Application of Plural Panelist Synthesis Method in Identifying Determinant Factors That Influence Economic Growth - Ardiyanto Maksimilianus Gai; Sri Purwati; Vivid Violin; Susanto; Mozart Malik Ibrahim (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to study intra-generational income mobility and poverty, and it also seeks to characterize and measure individual mobility by analyzing the duration of poverty, consecutive versus transient poverty, and the likelihood of re-entry. Researchers used a synthetic panel approach to estimate individual income in the second round based on data from the first round. This approach allows research to look at changes in individual income over time, even though actual panel data is unavailable. Based on research results, it show that the main factor influencing stagnation is the difficulty of leaving poverty, not the problem of entering poverty. In addition, analyses that consider the entire period also provide different results regarding the level of permanence in poverty. Synthetic panel analysis shows that the individuals who move out of poverty are those who were poor at the start of each period studied, not those who already had incomes above the poverty line. In addition, these results also show that the proportion of individuals who experience poverty in a shorter period is greater than that of those who experience poverty for four years. The analysis shows changes in poverty dynamics between the two periods studied. Successive poverty dominates, meaning that individuals who fall into poverty tend to remain poor over that period. However, the predominance is shifting towards transient poverty, where individuals experience poverty for shorter periods, moving in and out of poverty within that period.